SIKAP MULTIBAHASAWAN ORANG MEDAN DAN ANCAMAN PUNAHNYA BAHASA LOKAL - T. Syarfina (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
The less endangered language used by speakers of the overall too little, with a shift of functions which are gradually replaced by other languages. Language shift that occurred in the community in the field led to the extinction towards the Malay language. There are two indicators as facts and data that revealed a language shift to this, the pressure of the weight of the larger language isIndonesian, and early loss of speakers of children. On the other hand, the Malay language speakers (ethnic Malay) did not object when the community in North Sumatra has moved into Indonesian. This, given the forerunner of Indonesian is Malay.